Plectranthus amboinicus: A Systematic Review of Traditional Uses, Phytochemical Properties, and Therapeutic Applications - Márcia Santos Filipe; Gabrielle Bangay; Florencia Z. Brauning; Festus Oladayo Ogungbemiro; Bernardo Brito Palma; Ana María Díaz-Lanza; Amr Hassan; Rebeca André; Patricia Rijo (Pharmaceuticals)
Background: Coleus amboinicus (Lour.) (syn Plectranthus amboinicus) from the Lamiaceae family—a large family of aromatic herbs with many medicinally important species—is a frequently cited species within the Plectranthus genus, renowned for its traditional uses, phytochemical composition, biological activities, and applications in skin care. Methods: A systematic review was conducted following PRISMA guidelines to provide an in-depth understanding of P. amboinicus’ phytochemical composition and biological activity, particularly in dermatological contexts, underscoring its significance in traditional medicine and modern phytochemical research. Results: P. amboinicus extracts and essential oils exhibit significant antimicrobial activity against both Gram-positive and Gram-negative bacteria, and notable antifungal properties, particularly against dermatophytes. Additionally, the species demonstrates remarkable mosquito repellent and anti-parasitic effects, comparable to DEET, and potent anti-inflammatory properties by inhibiting pro-inflammatory cytokines. The plant’s rich polyphenolic content contributes to its significant antioxidant properties, preventing conditions like hyperpigmentation and premature aging. P. amboinicus also exhibits cytotoxic activity against various cancer cell lines and promotes wound healing through its analgesic, anti-inflammatory, and antioxidant abilities. Conclusions: This comprehensive exploration of P. amboinicus validates its diverse therapeutic potential across infectious diseases, oncology, and wound care. Further research and clinical trials are warranted to fully elucidate its mechanisms of action and optimize its therapeutic applications, paving the way for its integration into mainstream medical practices.